PROSPECTS OF GEOTHERMAL RESOURCES DEVELOPMENT FOR EAST CISCAUCASIA - A. B. Alkhasov; D. A. Alkhasova (Юг России: экология, развитие, 2014)
Abstract. Work subject. Aim. The Northern Caucasus is one of the prospective regions for development of geothermal energy.The hydrogeothermal resources of the only East Ciscaucasian Artesian basin are estimated up to 10000 MW of heat and 1000 MW of electric power. For their large-scale development it is necessary to built wells of big diameter and high flow rate involving huge capital investments. Reconstruction of idle wells for production of thermal water will allow to reduce capital investments for building of geothermal power installations. In the East Ciscaucasian Artesian basin there are a lot of promising areas with idle wells which can be converted for production of thermal water. The purpose of work is substantiation possibility of efficient development of geothermal resources of the Northern Caucasus region using idle oil and gas wells.Methods. The schematic diagram is submitted for binary geothermal power plant (GPP) with use of idle gas-oil wells where the primary heat carrier in a loop of geothermal circulation system is used for heating and evaporation of the low-boiling working agent circulating in a secondary contour of steam-power unit. Calculations are carried out for selection of the optimum parameters of geothermal circulation system for obtaining the maximum useful power of GPP. The thermodynamic analysis of low-boiling working agents is made. Development of medial enthalpy thermal waters in the combined geothermal-steam-gas power installations is offered where exhaust gases of gas-turbine installation are used for evaporation and overheat of the working agent circulating in a contour of GPP. Heating of the working agent in GPP up to the temperature of evaporation is carried out by thermal water.Results. The possibility of efficient development of geothermal resources of the Northern Caucasus region by construction of binary geothermal power plants using idle oil and gas wells is substantiated. The capacities and the basic characteristics of GPP in the promising fields are considered. Prospectivity of geothermal and steam-gas technologies is showed which allow using the low enthalpy thermal waters (80–100 оС) for electrical energy generation.Conclusions. 1. One of the ways of efficient involvement of geothermal resources in a power balance of the region is construction of the binary GPP using a fund of idle oil and gas wells. The capital expenditure for their reconstruction for production of thermal water is much lower than costs of construction of new wells. At the same time use of idle wells doesn't allow to receive big capacities on GPP because of restriction of a circulating flow rate because of small diameters of wells. Construction of binary GPP on existing wells will enhance energy security and reliability of power supply of socially important objects, will improve an ecological situation by replacement of organic fuel and will increase a share of renewable energy in a regional power balance. 2. Building of geothermal and steam-gas units will allow using the middle enthalpy thermal water for electric power generation, achieving the deeper temperature drop of thermal water that is important for improvement of the economic parameters of geothermal production and most effectively utilizing the heat of the gas-turbine exhaust gas.